2017
DOI: 10.1002/14651858.cd003188.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates in multiple myeloma: an updated network meta-analysis

Abstract: Bisphosphonates in multiple myeloma: an updated network meta-analysis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 172 publications
1
107
1
3
Order By: Relevance
“…The effect of a common bisphosphonate, zoledronic acid, was evaluated in the localized 5GTM1 model. Bisphosphonate treatment is commonly used in the clinic to improve bone quality and decrease skeletal‐related events in myeloma patients, and systematic literature reviews have shown that it ameliorates pain However, the quality of the pain data has recently been questioned because of the different read‐outs used in different trials and the lack of clinically significant analgesic effect in double‐blinded clinical trials . In the localized 5TGM1 model, systemic treatment with zoledronic acid protected the myeloma‐bearing bones from developing osteolytic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of a common bisphosphonate, zoledronic acid, was evaluated in the localized 5GTM1 model. Bisphosphonate treatment is commonly used in the clinic to improve bone quality and decrease skeletal‐related events in myeloma patients, and systematic literature reviews have shown that it ameliorates pain However, the quality of the pain data has recently been questioned because of the different read‐outs used in different trials and the lack of clinically significant analgesic effect in double‐blinded clinical trials . In the localized 5TGM1 model, systemic treatment with zoledronic acid protected the myeloma‐bearing bones from developing osteolytic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonate treatment is commonly used in the clinic to improve bone quality and decrease skeletal-related events in myeloma patients, and systematic literature reviews have shown that it ameliorates pain (48,49) However, the quality of the pain data has recently been questioned because of the different read-outs used in different trials and the lack of clinically significant analgesic effect in double-blinded clinical trials. (50) In the localized 5TGM1 model, systemic treatment with zoledronic acid protected the myelomabearing bones from developing osteolytic lesions. Bisphosphonate treatment also led to increased survival and partly ameliorated the pain-like behavior over time, suggesting that osteolytic bone lesions may play a role in pain development, but not be entirely responsible for it.…”
Section: Discussionmentioning
confidence: 99%
“…multiple myeloma or breast cancer) and often in conjunction with other anti‐cancer agents such as anti‐angiogenesis agents and/or systemic glucocorticoids. In multiple myeloma, a meta‐analysis of 24 studies found that about 1 in 1000 patients in bisphosphonate myeloma studies developed ONJ . Though the incidence rates of ONJ in the dosing regimens used for osteoporosis has varied substantially between different observational studies, it has generally been found to be tenfold lower than for the cancer regimes .…”
Section: Antiresorptivesmentioning
confidence: 99%
“…34,35 In addition to this, bisphosphonates that are a well-established part of the treatment of MM patients, are known to reduce pathological vertebral fractures, skeletal-related events and pain. 36 Moreover, zoledronic acid, that was approved for MM in the latter calendar period of the study has shown a positive effect on overall survival. 13 In 2010, Swedish national guidelines recommended treatment with bisphosphonates from the time of MM diagnosis for all MM patients, irrespective of the presence of bone disease, and in the years 2008 to 2015, over 70% of MM patients received bisphosphonates as a part of their management.…”
Section: Our Analyses On Different Subgroups Of Fractures In MM Patiementioning
confidence: 97%